ANALISIS KADAR KOTORAN, KADAR AIR DAN INTI MASAK PADA INTI SAWIT DI PT. KEDATON MULIA PRIMAS MENGGUNAKAN METODE REGRESI LINIER BERGANDA - Zahrotunnisa, Vista (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2024)
The main production of oil palm plants is fruits. Vegetable oil made from fruits Palm oil consists of CPO (Crude Palm Oil) and PKO (Palm Kernel Oil) derived from kernels. palm oil (endocarp). Palm kernel (kernel) is a superior product with high selling value and is further refined into palm kernel oil. This affects the quality of the kernel. water and dirt content during temporary storage in the core tank before being sent to partners. . The quality of palm kernel oil affects the quality of palm kernel oil. This study aims to determine the effect of moisture and dirt content on the quality of palm kernel in the core tank. Social purpose This research was conducted by PT. Kedaton Mulia Primas The two methods used in this study are the separation of dirt content and the method to determine the moisture content in palm kernel using the Moisture Analyzer Balance Tool with the principle of evaporation.